AN ANALYSIS OF SOCIAL DEIXIS IN THE DRESSMAKER MOVIE - Nusi Heriyadi; Eli Diana (UNIVED Press, 2020)
Humans need a language to communicate to each other, whether it is in spoken or written language. Human beings can better interact with each other and in compliance with social norms with an awareness of sociolinguistics. The researchers of this study concentrated on sociolinguistics in this review, especially pragmatics, which includes social deixis. This research aimed to investigate the role and the function of social deixis in “The Dressmaker” movie. This study is a qualitative descriptive study by collecting data from the conversations in “The Dressmaker” movie. The data were analyzed based on Levinson's theory of the type of social deixis and Hollinghead’s theory of the function of social deixis. Furthermore, the data were also analyzed by using Spradley's theory. There were three steps taken in using this theory, namely domain analysis, taxonomic analysis and component analysis. After analyzing, the reseachers found 2 types of social deixis in the movie